The complete chloroplast genome sequence of Pyrus phaeocarpa Rehd. Issue 1 (2nd January 2019) - Xiang, Qiu-Hong; Zhang, Dong-Xu; Wang, Qing; Wang, Xin-Rui; Guan, Wen-Bin
Abstract: Pyrus phaeocarpa Rehd. belongs to the Pyrus genus (Rosaceae) with high commercial value in China. Many trees in the wild have been destroyed affected by human activities and needed to be protection urgently. In this study, we reported the complete chloroplast genome sequence of P. phaeocarpa using Illumina sequencing technology. The complete chloroplast genome of P. phaeocarpa was 160, 203 bp in length, containing a large single copy (LSC, 88, 200 bp), a small single copy (SSC, 19, 231 bp), and a pair of inverted repeats (IRs, 26, 385 bp). The chloroplast genome GC content was 36.54%, contained 113 unique genes, including 30 tRNA, four rRNA, and 79 protein-coding genes. Phylogenetic analysis revealed that P. phaeocarpa was close to P. pashia, P. pyrifolia, and P. ussuriensis, provided strong support for the relationship of Pyrus .